Day 2 Tue, November 10, 2020 2020
DOI: 10.2118/202636-ms
|View full text |Cite
|
Sign up to set email alerts
|

Fishbone Stimulation a Game Changer for Tight Carbonate Productivity Enhancement, Case Study of First Successful Implementation at Adnoc Onshore Fields

Abstract: Productivity enhancement of tight carbonate reservoirs (permeability 1-3 md) is critical to deliver the mandated production and to achieve the overall recovery. However, productivity improvement with conventional acid stimulation is very limited and short-lived. Tight reservoirs development with down spacing and higher number of infill wells can increase the oil recovery. Nevertheless, poor vertical communication (Kv/Kh < 0.5) within the layered reservoir is still a challenge for productivity enhancemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Various studies have shown the successful application of fishbone well designs in different regions and geological formations, including Russia's Vankorskoe Field [19], Abu Dhabi National Oil Company's (ADNOC) onshore field in a tight carbonate formation [20], Aasgard Field in Norway [21], and Vostochno-Messoyakskoye onshore field in Russia [22]. Productivity enhancements were also observed in the United Arab Emirates (UAE) with a 300% increase during the application of fishbone well technology in a very tight reservoir [23].…”
Section: Fishbone Technology Field Studiesmentioning
confidence: 99%
“…Various studies have shown the successful application of fishbone well designs in different regions and geological formations, including Russia's Vankorskoe Field [19], Abu Dhabi National Oil Company's (ADNOC) onshore field in a tight carbonate formation [20], Aasgard Field in Norway [21], and Vostochno-Messoyakskoye onshore field in Russia [22]. Productivity enhancements were also observed in the United Arab Emirates (UAE) with a 300% increase during the application of fishbone well technology in a very tight reservoir [23].…”
Section: Fishbone Technology Field Studiesmentioning
confidence: 99%
“…One is that severe losses happened based on FCS experience in the field [15][16][17][18][19][20]. Another is a significant risk for fishing basket needle recovery as it is failed case [21].…”
Section: Option D Fish-bone Completionand Stimulation Technologymentioning
confidence: 99%
“…Four additional case studies from Russia have been documented in the literature, including sandstone formations in the Vostochno-Messoyakskoye onshore field [17], low permeable formations in the East Messoyakha field [18], the Vankor oilfield in Krasnoyarsk, Eastern Siberia [19], and the Srednebotuobinskoye oil and gas condensate field in Eastern Siberia [20]. In the UAE, successful FbD case studies have been reported in naturally fractured reservoirs [21,22], and an innovative Fishbone infill well was applied in the Canadian oil sands play [23]. Research into applications of Fishbone well configurations in areas such as geothermal drilling, enhanced oil recovery, steam-assisted gravity drainage, and underground saltwater disposal are ongoing [24,25].…”
Section: Introductionmentioning
confidence: 99%